Vertical transport through n-As/p-GaSb heterojunctions at high pressures and magnetic fields - Chaudhry, W; Chaudhry, Wahid (1999)
﻿ The conduction band of InAs lies lower in energy than the GaSb valence band. In order to preserve continuity of the Fermi level across the interface, charge transfer takes place resulting in a confined quasi two dimensional electron gas (2DEG) in the InAs and a confined quasi two dimensional hole gas (2DHG) in the GaSb. This study is an investigation into the vertical transport in an n-InAs/p-GaSb single heterojunction (SHET). Application of a forward bias (InAs negative with respect to GaSb) increases the 2DEG and 2DHG concentrations and, therefore, their confinement energies. Eventually a critical bias is reached where the electron confinement energy moves above the hole confinement energy (the theoretical voltage induced semimetal/semiconductor transition Vc). Any subsequent increase in voltage is expected to result in a current decrease, and a region of negative differential resistance (NDR) should occur. The SHET can be grown with two distinct interface types, 'InSb-like' and 'GaAs-like'. This in turn affects the vertical transport characteristics of each type. Experimental IV traces at various pressures are compared with the corresponding results from sophisticated self-consistent band profile calculations taking into account band mixing effects for the first time through a k.p theory framework. Experimental IV traces of the SHETs under a magnetic field parallel to the interface are also compared with results from calculations that take into account the coupling of the growth and in-plane electron and heavy hole motions. Both sets of analysis support earlier conclusions that NDR occurs after Vc for both interfaces, and that each interface supports a different conduction mechanism. Evidence of multiple phonon processes occurring in both sample types is observed for the first time and is proposed to reconcile the above experimental observations with theory. This data is found to offer explanations for a number of other observations. Field perpendicular to the interface leads to the observation of features beyond the NDR region in both sample types. In samples with an 'InSb-like' interface, applying additional hydrostatic pressure leads to very strong features beyond the main NDR. Through a complex self-consistent decoupled model taking into account electrons and heavy holes, all these features are proposed to be due to a filling of an integer number of Landau levels. The band profile is predicted to alter dramatically at this point. The same model explains the observation of weaker features at 1 bar at high fields (~ 40T). A variation of NDR position is found with a rotation of an-plane field.